The Use of Reverse Engineering Method in Designing Palm Fruit Collection Tools - Kurniawan, Fajar; Yola, Melfa; Nazaruddin, Nazaruddin; Harpito, Harpito; Umam, Muhammad Isnaini Hadiyul (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
Product planning, design, and development are essential phases in manufacturing, starting from conceptualization and system design to production, testing, and ultimately delivering superior products that meet consumer demands. For instance, in the oil palm plantation industry, efficient tools play a vital role. Harvesting significantly affects the quality of oil palm yields, with losses often occurring due to loose fruit detachment from the Fresh Fruit Bunches (FFB), which fall to the ground. These loose fruits, known as "berondolan," are just as valuable as those still attached to the FFB and contribute substantially to farmers' income. Currently, farmers must manually collect these fallen fruits from beneath each tree, which is time-consuming. To address this issue, the study introduces a harvesting tool designed through reverse engineering for gathering loose oil palm fruits. After processing and analysis, the proposed tool incorporates modifications, particularly in the roller section, where two 10 cm diameter stainless steel drain holes are added. Additionally, it features two 6.5 cm diameter iron drives, enhancing efficiency by increasing collection capacity by 1.5 kg per minute compared to conventional drain hole designs. Keywords: Brondolam, Design, Efficient, Palm fruit collection tool, Oil Palm, Reverse engineering.